Stochastic scenario‐based model and investigating size of energy storages for PEM‐fuel cell unit commitment of micro‐grid considering profitable strategies. Issue 7 (1st July 2014) - Mohammadi, Sirus; Mozafari, Babak; Solymani, Soodabe; Niknam, Taher
Abstract : This paper presents a unit commitment formulation for micro‐grid that includes a significant number of grid parallel Proton Exchange Membrane‐Fuel Cell Power Plants (PEM‐FCPPs) with ramping rate and minimum up/down time constraints. The aim of this problem is to determine the optimum size of energy storage like battery storages and use the efficient hydrogen and thermal energy storages and to schedule the committed units' output power while satisfying practical constraints and electrical/thermal load demand over one day with 15 min time step. In order to best use of multiple PEM‐FCPPs, hydrogen storage management is carried out. Also, since the electrical and heat load demand are not synchronised, it could be useful to store the extra heat of PEM‐FCPPs in the peak electrical load in order to satisfy delayed heat demands. Due to uncertainty nature of electrical/thermal load, photovoltaic and wind turbine output power and market price, a two‐stage scenario‐based stochastic programming model, where the first stage prescribes the here‐and‐now variables and the second stage determines the optima value of wait‐and‐see variables under cost minimization is implemented. For solving the problem, a new enhanced cuckoo optimisation algorithm is presented and successfully applied to two typical micro‐grids. Quantitative results show its usefulness.